2019
DOI: 10.1038/s41598-019-47868-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose Levamlodipine Besylate in the treatment of vascular dementia

Abstract: Vascular dementia (VaD) is a complex disorder caused by reduced blood flow in the brain. However, there is no effective pharmacological treatment option available until now. Here, we reported that low-dose levamlodipine besylate could reverse the cognitive impairment in VaD mice model of right unilateral common carotid arteries occlusion (rUCCAO). Oral administration of levamlodipine besylate (0.1 mg/kg) could reduce the latency to find the hidden platform in the MWM test as compared to the vehicle group. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, this study also found that the total antihypertensive efficiency of the three‐drug combination regimen at different times was 91.24% and 87.10% for morning and night medication groups, respectively, and they all contributed to blood pressure reduction and improvement of vascular endothelial function and circadian rhythm of blood pressure, which are related to the mechanism of action of the three drugs: (1) Irbesartan can relax blood vessels, reduce the burden on the heart, and restore the circadian rhythm of normal blood pressure, thus correcting the “non‐dipper” curve of blood pressure; it can promote the dilatation of precapillary arteries, resistance arteries and veins, reduce anterior and posterior loads on the heart, thus improving ventricular remodeling and avoiding myocardial hypertrophy and vessel wall thickening caused by long‐term hypertension 17 , 18 ; (2) Hydrochlorothiazide can reduce intracellular calcium ion and sodium‐calcium exchange in vascular smooth muscle, decrease intracellular calcium ion and vascular smooth muscle responsiveness to angiotensin and catecholamines, weaken vasoconstriction, and thus reduce blood pressure; its sustained hypotensive effect may be related to the local release of prostaglandins or other vasodilating substances that reduce small artery dilation and total peripheral resistance 19 , 20 ; (3) Levamlodipine can block L‐type calcium channels and inhibit the transfer of calcium ions into the cells, thus exerting a direct diastolic effect on vascular smooth muscle, improving hemodynamics and regulating blood pressure 21 ; Levamlodipine promotes the release of NO and other potent vasodilatory substances, indirectly diastaging vascular smooth muscle and thus improving vascular endothelial function. Long‐term use of hydrochlorothiazide can produce dose‐related side effects such as elevated uric acid levels, abnormal glucose tolerance, hypokalemia, and reduced insulin sensitivity, while the irbesartan and levamlodipine combination can reduce or counteract the RAAS and sympathetic nerves activation caused by long‐term use of hydrochlorothiazide, which increases the antihypertensive effect and reduces adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study also found that the total antihypertensive efficiency of the three‐drug combination regimen at different times was 91.24% and 87.10% for morning and night medication groups, respectively, and they all contributed to blood pressure reduction and improvement of vascular endothelial function and circadian rhythm of blood pressure, which are related to the mechanism of action of the three drugs: (1) Irbesartan can relax blood vessels, reduce the burden on the heart, and restore the circadian rhythm of normal blood pressure, thus correcting the “non‐dipper” curve of blood pressure; it can promote the dilatation of precapillary arteries, resistance arteries and veins, reduce anterior and posterior loads on the heart, thus improving ventricular remodeling and avoiding myocardial hypertrophy and vessel wall thickening caused by long‐term hypertension 17 , 18 ; (2) Hydrochlorothiazide can reduce intracellular calcium ion and sodium‐calcium exchange in vascular smooth muscle, decrease intracellular calcium ion and vascular smooth muscle responsiveness to angiotensin and catecholamines, weaken vasoconstriction, and thus reduce blood pressure; its sustained hypotensive effect may be related to the local release of prostaglandins or other vasodilating substances that reduce small artery dilation and total peripheral resistance 19 , 20 ; (3) Levamlodipine can block L‐type calcium channels and inhibit the transfer of calcium ions into the cells, thus exerting a direct diastolic effect on vascular smooth muscle, improving hemodynamics and regulating blood pressure 21 ; Levamlodipine promotes the release of NO and other potent vasodilatory substances, indirectly diastaging vascular smooth muscle and thus improving vascular endothelial function. Long‐term use of hydrochlorothiazide can produce dose‐related side effects such as elevated uric acid levels, abnormal glucose tolerance, hypokalemia, and reduced insulin sensitivity, while the irbesartan and levamlodipine combination can reduce or counteract the RAAS and sympathetic nerves activation caused by long‐term use of hydrochlorothiazide, which increases the antihypertensive effect and reduces adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Levamlodipine can block L-type calcium channels and inhibit the transfer of calcium ions into the cells, thus exerting a direct diastolic effect on vascular smooth muscle, improving hemodynamics and regulating blood pressure21 ; Levamlodipine promotes the release of NO and other potent vasodilatory substances, indirectly diastaging vascular smooth muscle and thus improving vascular endothelial function. Long-term use of hydrochlorothiazide can produce doserelated side effects such as elevated uric acid levels, abnormal glucose tolerance, hypokalemia, and reduced insulin sensitivity, while the irbesartan and levamlodipine combination can reduce or counteract the RAAS and sympathetic nerves activation caused by long-term use of hydrochlorothiazide, which increases the antihypertensive effect and reduces adverse effects 22.…”
mentioning
confidence: 99%
“…Then, in vivo and in vitro VaD models were applied to evaluate the exact efficacy and the mechanism of Cur20. As an important type of vascular dementia, subcortical ischemic vascular dementia is usually produced in animal models, such as bilateral permanent common carotid artery occlusion (2-VO) in rats and right common carotid artery occlusion in mice (Yao et al, 2019). In view of the characteristics of 2-VO experimental animals, such as high mortality, serious injury of motor system, and difficult detection of behavioral indicators, we chose the rUCCAO model with simple operation, low mortality, good repeatability and little trauma.…”
Section: Introductionmentioning
confidence: 99%